ANALISIS KINERJA KEUANGAN DENGAN MENGGUNAKAN METODE CAMEL PADA PT. BANK SULSELBAR - Ibrahim Ibrahim (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2014)
This study aims to determine the financial performance. Bank Sulselbar years 2009-2011 by using the CAMEL. The method of analysis used in this study is descriptive, ie by analyzing financial statements using the CAMEL method in assessing the performance of companies on the PT. Bank Sulselbar. The results of the study showed that ; aspect ratio of capital as measured by Capital Adequacy Ratio (CAR) during 2009 to 2011 was ranked 1 or log in predicate healthy. This is because the value of the CAR above the standard minimum capital obligations is above 8%. Aspects of asset quality as measured by the ratio of Non Performing Assets (APB) during 2009 to 2011 was ranked 1 or log in predicate healthy . This is because the value of the ratio achieved APB does not exceed 5%, in accordance with the standards set by Bank Indonesia . Aspects of asset quality as measured by the ratio of non-performing loans (NPLs) during 2009 to 2011 was ranked 1 or log in predicate healthy. This is because the value of the NPL ratio has achieved the minimum standards of Bank Indonesia because they have NPL ratios below 5%. Aspects of profitability as measured by ROA ratio during 2009 to 2011 was ranked 1 or log in predicate healthy. This is because the value achieved ROA was 1.25% above the bank's health standards compliant according to Bank Indonesia. Aspects of profitability as measured by ROA ratio during 2009 to 2011 was ranked 1 or log in predicate healthy. This is because the value of ROA ratio is achieved not exceed 93.5%, in accordance with the standards set by Bank Indonesia. Aspects of liquidity as measured by the ratio LDR during 2009 to 2011 was ranked 4 or log in less healthy predicate. This is because the LDR value achieved is between 100% - 120%